Clinical Diagnosis of Sydenham's Chorea in Area Endemic for Acute Rheumatic Fever - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2006)
A retrospective chart review to determine the causes of childhood chorea was conducted in the Division of Allergy, Immunology and Infectious Disease at the Children's Hospital of Pittsburgh, PA.